Reproductive Outcomes After Hysteroscopic Septolysis: A Single Center Experience - AlKhalidi, Batool A. Hashim (Medical Science Journal for Advance Research, 2026)
Back ground: hysteroscopic septolysis is a minimally invasive procedure aiming at improving reproductive outcomes in symptomatic women; however: the effectiveness of the procedure has been requestioned recently. Aim of study: this study is designed to evaluate the reproductive outcomes of hysteroscopic septolysis in women diagnosed with partial and complete uterine septa. Design: a retrospective case series study.Setting: a private infertility treatment center in Annajaf El Ashraf governorate –Iraq. Population of patients: All patients proved to have partial or complete uterine septa during a period from February 2022 till April 2024 with variable period of patients follow up. Patients and Methods: A prospective case series of 32 patients with a confirmed diagnosis of a septate uterus (both partial and complete) who are undergoing hysteroscopic septolysis in one center in Annajaf AL Ashraf Governorate, Iraq, from February 2020 to August 2024. The study included women aged 18-40 years who attempted to conceive post-operatively. Data were collected through a specified questionnaire, clinical examinations, and relevant investigations. Reproductive outcomes, including the time to conception, pregnancy rates, and pregnancy outcomes abortion, preterm birth, and term live birth, are recorded and analyzed. Results: Spontaneous pregnancies occurred in 15.625% of patients, and 40.625% were still on postoperative hormonal treatment. Successful pregnancy was achieved in 43.75% of patients, with 78.6% delivering via cesarean section and 21.4% via vaginal delivery. The majority of successful pregnancies resulted in singleton births (85.8%), with 7.1% twin pregnancies and 7.1% miscarriages. The mean age of participants was 28 ± 3.93 years. The majority (65.6%) had primary infertility, with a mean infertility duration of 6.82 ± 3.80 years. Partial septum was present in 93.75% of cases, while 6.25% had a complete septum. Intraoperative and postoperative complications were minimal. Post-procedure, 43.75% of patients underwent ICSI, with a 64.3% clinical pregnancy rate. Conclusion: Hysteroscopic septolysis is a safe and effective procedure for improving reproductive outcomes in women with a septate uterus. The procedure is associated with improved pregnancy rate and outcomes, and with minimal complications, making it a valuable treatment option for women with this congenital anomaly.